India's development scenario : challenges and prospects - National Seminar on India's Social, Political and Economic Development: Challenges, Achievements, and Ways Ahead (2006 : Madhya Pradesh Institute of Social Science Research, Ujjain); Sisodia, Yatindra Singh; Madhya Pradesh Institute of Social Science Research, Ujjain (Jaipur : Rawat Publications, 2009)
Contributed articles presented at the National Seminar on India's Social, Political and Economic Development: Challenges, Achievements, and Ways Ahead May 24-26, 2006 at Madhya Pradesh Institute of Social Science Research, Ujjain.
Includes statistical tables.
Includes bibliographical references.
Keywords: INDIAS DEVELOPEMENT; SCENARIO--INDIA; DEVELOPEMENT; INDIA -- ECONOMIC POLICY -- CONGRESSES; INDIA -- ECONOMIC CONDITIONS -- CONGRESSES; INDIA -- SOCIAL POLICY -- CONGRESSES; INDIA -- SOCIAL CONDITIONS -- CONGRESSES